Budaya Betangkant Anak Dalam Suku Dayak Keninjal Sebagai Upaya Kontektualisasi Kasih Allah - H Herwinasastra (Sekolah Tinggi Teologi Simpson, 2019)
The purpose of this paper is to analyze a culture of Betangkant Children of the Keninjal Dayak tribe as an effort to contextualize the good news. The study of the meaning and cultural aspects of raising children in an effort to apply the gospel or good news in the context of the life of the Dayak Keninjal community. Through the culture of Betangkant Children in the Keninjal tribe, Madyaraya Village gives meaning and an entrance to evangelism for Dayak Keninjal to accept Jesus Christ as Savior in his life and figure of a Father who loves His Son. God created humans with creativity to be cultured, and with the framework of human culture looking at God and accepting God's self-revelation through filters and a framework that was intact in culture. Sustainability of God's covenant relationship with His people in all times and in all contexts. The culmination of this agreement is the Lord Jesus, who brought a new covenant to His people. Tujuan penulisan ini adalah untuk menganalisis sebuah budaya Betangkant Anak Dayak Keninjal sebagai upaya kontekstualisasi kabar baik. Pengkajian aspek arti dan nilai budaya mengangkat anak dalam upaya penerapan Injil atau kabar baik dalam kontek kehidupan masyarakat Dayak Keninjal. Melalui budaya Betangkant Anak di suku Keninjal, desa Madyaraya memberikan makna dan pintu masuk penginjilan bagi suka Dayak Keninjal untuk menerima Yesus Kristus sebagai Juruselamat dalam kehidupanya dan figure seorang Bapa yang mengasihi Anak-Nya. Allah menciptakan manusia dengan kreatifitas untuk berbudaya, dan dengan kerangka budaya manusia memandang Allah dan menerima penyataan diri Allah melalui filter dan kerangka yang utuh budaya. Keberlangsungan hubungan perjanjian Allah dengan umat-Nya di segala waktu dan segala konteks. Puncak dari perjanjian ini adalah Tuhan Yesus, yang membawa perjanjian baru bagi umat-Nya.